2009
DOI: 10.1007/s10725-009-9379-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential plant growth and osmotic effects of two maize (Zea mays L.) cultivars to exogenous glycinebetaine application under drought stress

Abstract: We investigated the effects of exogenous glycinebetaine (GB) and drought stress (DS) on grain yield (GY) and production of dry matter (DM) and osmolytes in two maize (Zea mays L.) cultivars i.e. Shaandan 9 (S 9 ) and Shaandan 911 (S 911 ) during the entire growing period. Drought stress substantially reduced DM and GY but increased free proline, endogenous GB, soluble sugar and K ? concentrations in leaves of both cultivars. The DM production, GY, drought index (DI) and concentrations of these osmolytes were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…When plants are subjected to environmental stress including heat stress, a variety of ROS are generated [117,118]. These ROS interfere with different organic molecules, resulting in the reduction of photosynthesis and subsequently reduced plant growth [117,119]. Under heat stress, plants are capable of counteracting ROS generation by the production of different antioxidant molecules (enzymatic and non-enzymatic) [117,118].…”
Section: Plos Onementioning
confidence: 99%
“…When plants are subjected to environmental stress including heat stress, a variety of ROS are generated [117,118]. These ROS interfere with different organic molecules, resulting in the reduction of photosynthesis and subsequently reduced plant growth [117,119]. Under heat stress, plants are capable of counteracting ROS generation by the production of different antioxidant molecules (enzymatic and non-enzymatic) [117,118].…”
Section: Plos Onementioning
confidence: 99%
“…Glycine betaine not only acts as an osmoregulator but also stabilizes the structures and activities of enzymes and protein complexes and maintains the integrity of membranes against the damaging effects of drought [11]. It has been shown that exogenous application of GB could be a promising way to directly maintain and enhance the growth and yield of maize [12][13][14]. Water deficit conditions alter the growth pattern of plants with inhibition in development both qualitatively and quantitatively [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Independent roles of NO and GB in abiotic stress are known. [35][36][37][38] Earlier investigations have revealed that endogenous NO derived from nitric oxide synthase (NOS)-like activity in plants can have a possible role in maintaining osmolyte accumulation. 16,39 Inhibition of NOS activity affects GB accumulation in maize.…”
Section: Discussionmentioning
confidence: 99%